War Violence Exposure and Tax Compliance - Sergio Galletta; Tommaso Giommoni (CESifo GmbH, 2024)
We explore the effects of exposure to conflict and violence on civic compliance with the law. Using newly digitized historical records of income declarations and tax audits from post-World War I Italy, we show that losing a relative as a direct result of the war reduces tax compliance. To account for the potential endogeneity of the treatment, we use an instrumental variable strategy exploiting the exogenous allocation of soldiers to more/less dangerous military units. Our results show that the effect of reduced tax compliance remains consistent across different measures of compliance and is not due to economic reasons. We also find that this negative impact is lessened when the state acknowledges the sacrifice of the deceased, in communities that suffered many casualties, or in areas with high levels of social cooperation before the war. Overall, our findings suggest that war can erode social norms, leading to a lower willingness to contribute to public goods, such as paying taxes.
Keywords: 330; Tax morale; War; Mortality; Family; Italy